High scintillation yield and fast response to alpha particles from thin perovskite films deposited by pulsed laser deposition - Caricato, Anna Paola; Moretto, Sandra; Guascito, Maria Rachele; Quarta, Gianluca; Mazzeo, Marco; Favaro, Matteo; Rizwan Aziz, Muhammad; Provenzano, Chiara; Marra, Marcella; Cesaria, Maura; Polo, Matteo; Delgado, Jessica; et al. (Frontiers in Physics, 2022)
Although the field of solar cells is the most popular application of perovskite materials, their use in radiation detection applications is emerging. The success of perovskites as radiation detectors rests partly on the same material properties that have led to successful optoelectronics applications, meaning that other specific properties, like large stopping power, high mobility lifetime product, fast response, and large bulk resistance, play a role. In this respect, inorganic perovskites are attracting a lot of attention as scintillator materials with performances sensitive to material shape (single crystals, nanocrystals, and thin films) and growth methods. In this study, we report on the morphological, structural, and optical response of thin CsPbBr3-based perovskite films, deposited by Pulsed Laser Deposition (PLD) and post-growth annealed at 350°C in air, following excitation by different particle sources. The annealing treatment resulted in a prompt structural refinement, grain growth, and oxygen bonding to the Pb phase together with an enrichment of the surface in chemo-adsorbed oxygen probably due to Cs–O interactions, as evidenced by X-ray photoelectron spectroscopy. The film behavior under 2 MeV H+ ion beam irradiation at different fluences was analyzed together with its scintillation properties following an interaction with α particles from an Am-241 radioactive source demonstrating a very fast response for an inorganic material (∼5ns) and a photoelectron yield of about ∼47% with respect to a commercial CsI:Tl scintillator.